Pretend play workshop for kids a year of DIY craft projects and open-ended screen-free learning for kids ages 3-7 - Kruse, Caitlin; Roberson, Amanda; Johnson, Emma (Quarry Books, 2023)
"Pretend Play Workshop for Kids offers a year of screen-free dramatic play scenarios for adults to set up and kids to engage with, featuring open-ended making and learning"--